Managing Public Debt : From Diagnostics to Reform Implementation - World Bank (Washington, DC: World Bank, 2012)
Managing Public Debt will serve government officials contemplating or in the process of reforming their practices, providers of technical assistance, and practitioners working on building capacity in public debt management. Because effective implementation of debt management strategies also requires a developed domestic government debt market, readers will also be interested in the companion volume, Developing the Domestic Government Debt Market, published by The World Bank in February 2007, based on the same joint pilot program.